Value chains: A new voice on the market - Bon, Anna; Boyera, Stéphane (Technical Centre for Agricultural and Rural Cooperation, 2012)
A project to improve environmental conditions for farmers in West Africa is developing a voice-based market information system. The Web Alliance for Regreening in Africa intends to develop the system further to create a speech-operated world wide web